Population pharmacokinetic and pharmacodynamic analysis of plasma Aβ40 and Aβ42 following single oral doses of the BACE1 inhibitor AZD3839 to healthy volunteers. Issue 5 (26th May 2014) - Quartino, Angelica; Huledal, Gunilla; Sparve, Erik; Lüttgen, Maria; Bueters, Tjerk; Karlsson, Pär; Olsson, Tina; Paraskos, Jonathan; Maltby, Justine; Claeson‐Bohnstedt, Kristina; Lee, Chi‐Ming; Alexander, Robert; et al.
Abstract Modulating deposition of Aβ‐containing plaques in the brain may be beneficial in treating Alzheimer's disease. β‐site amyloid precursor protein cleaving enzyme 1 (BACE1) inhibitors have been shown to reduce Aβ in plasma and CSF in healthy volunteers. In this study safety, pharmacokinetics and pharmacodynamics that is reduction of the plasma biomarkers Aβ40 and Aβ42, of the BACE1 inhibitor AZD3839 were evaluated. Single oral ascending doses (1–300 mg) of AZD3839 were administered to 54 young healthy volunteers in a randomized, double‐blind, placebo‐controlled study. The data was analyzed using non‐linear mixed effects modeling. AZD3839 reduced Aβ40 and Aβ42 in plasma with estimated potencies (EC50) of 46 and 59 nM, respectively, and a maximum effect of approximately 55%. This was in excellent agreement with the concentration–response relationships obtained in mouse and guinea pig. AZD3839 exposure displayed non‐linear kinetics, described by a three‐compartment model with a saturated binding compartment and an increase in bioavailability with dose. AZD3839 was safe, although, a dose‐dependent QTcF prolongation was observed (mean 20 milliseconds at 300 mg). In conclusion, AZD3839 reduced plasma Aβ40 and Aβ42, demonstrating clinical peripheral proof of mechanism. Pre‐clinical models were predictive for the effect of AZD3839 on the human plasma biomarker in a strictly quantitative manner.